Demanda de educación o de ciudadanía? - Miguel Fernández M. (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2005)
La demanda de educación depende del conjunto de decisiones que toman los hogares, pero en el área rural la decisión de demandar educación debe ser puesta en un contexto adecuado. Por una parte, la alta participación de menores en actividades destinadas a generar ingresos, hace que, en principio, la demanda de educación deba ser considerada como una no oferta de trabajo. Las decisiones de trabajar en el área rural, a su turno, dependen de la tenencia de tierras y/o de ganado y de las estrategias de los hogares para obtener ingresos, en un escenario caracterizado por la descomposición de la economía campesina. – – The drop social mobility and the drop educational quality in Bolivia, they are elements that are reinforced to each other, creating barriers to achieve higher economic rates of growth and to reduce the poverty. In spite of it, the homes have decided to invest in the human capital of their children. The decision of investing in education, especially in university education, although it reflects the behavior maximizador of the individuals, it is a decision affected by the conditions of the home, being been able to say that is a decision of the home like unit. In that mark, it is observed that the homes, independently of their entrance level, they would be betting for the university education, in that sense the private education has entered to compete strongly with the public education; however, the lack of appropriate information is observed so that the decisions are the best.
Keywords: 330; Bildungsverhalten; Ländlicher Raum; Bolivien